The Effect of Promotion on Purchasing Decisions at PT. Auto 2000 Bintaro - Mas’adi, Mahnun (Universitas Negeri Makassar, 2020)
This study aims to determine the effect of promotion on purchasing decisions at PT. AUTO 2000 Bintaro. The method used is explanatory research with a sample of 85 respondents. The analysis technique uses statistical analysis with regression testing, correlation, determination, and hypothesis testing. The results of this research variable Promotion obtained an average score of 3.42 with good criteria. The purchasing decision variable obtained an average score of 3.83 with good criteria. The promotion has a significant effect on purchasing decisions with the regression equation Y = 8.949 + 0.862X, and a correlation value of 0.772 or strong with a determination of 59.5%. Hypothesis testing obtained a significance of 0.000 <0.05.